2006
DOI: 10.1007/s00167-006-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry of the medial tibial condyle to design the tibial component for unicondylar knee arthroplasty for the Korean population

Abstract: Unicondylar knee arthroplasty (UKA) has gained popularity in the recent years for treating medial compartment osteoarthritis of the knee joint in the Asian population. There is little information about the anthropometry of the resected bony surfaces of the knee joint in these population groups for designing the appropriate size-matched UKA components. We studied the anthropometry of the resected medial tibial condyles in 50 male and 50 female Korean cadavers by using three-dimensional computer tomography. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 11 publications
6
35
6
Order By: Relevance
“…Designing of prosthesis considering the gender difference have been advocated in Chinese population by Cheng et al 18 whereas Surendra et al 11 showed a progressive decline in the condylar aspect ratio with the increase in the AP dimension, irrespective of gender. 13 Westrich et al suggested that asymmetrical smaller lateral condylar surface produces better outcome compared with the symmetrically constructed prosthesis. 15 Limitation of this study is that it was performed on dry bones which may have undergone shrinkage in its morphology as compared with live specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Designing of prosthesis considering the gender difference have been advocated in Chinese population by Cheng et al 18 whereas Surendra et al 11 showed a progressive decline in the condylar aspect ratio with the increase in the AP dimension, irrespective of gender. 13 Westrich et al suggested that asymmetrical smaller lateral condylar surface produces better outcome compared with the symmetrically constructed prosthesis. 15 Limitation of this study is that it was performed on dry bones which may have undergone shrinkage in its morphology as compared with live specimens.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports to date that suggest a link between early tibial implant failure and insufficient bone coverage even though we may expect that cortical bearing of the tibial component should be better. Few studies [5,16] have analyzed the correlation between tibial anatomy and implant design for UKA. Fitzpatrick et al [5] measured the shape of the tibial plateau by modeling of the tibial resection as described by Surendran et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies on knee anthropometry, the measurements were made on normal subjects. 22 But in clinical practice, measurement of arthritic knees would be more helpful because there would be associated dysplasia of the femoral and/or the tibial condyles. Since we measured the dimensions before any resections were made, the values correspond to the original anatomy of the knees and can be used diversely.…”
Section: Discussionmentioning
confidence: 99%